Mountain geo facts - Howell, Izzi (Geofacts (Crabtree Publishing Company), 2018)
Provides simple geological facts about mountains, such as how they form, their impact on the climate, and their flora and fauna. Includes colorful illustrations, profiles of different mountain ranges, a glossary, a text-dependent quiz, sources for further learning, and an index.